Exploring Building Religious Character Through Religious Activities for Students at MTs Muslimat NU Palangka Raya - Noormila, Cahya; Muslimah, Muslimah; Surawan, Surawan (UMSU, 2025)
This article aims to explore how to build religious character through muhadharah religious activities. The research method used is descriptive qualitative with subjects 3 students and 1 teacher MTs Muslimat NU Palangka Raya, with data collection techniques through observation, interviews, and documentation, and with data analysis following Miles and Huberman, there are four stages that must be done, namely; collecting data, reducing data, presenting data, and conclusions. The results of the study indicate that muhadharah activities, as a habit of noble morals in the school environment consistently have an impact on building students' religious character. Through these activities, students not only understand religious teachings theoretically, but are also able to internalize religious values in life. This study recommends that religious activities be used as a main pillar in the strategy for developing religious character in the school environment. The results of the research conducted by the researcher, through observation, interviews and documentation, the researcher found that religious activities such as muhadharah are able to build the religious character of students at MTs Muslimat NU Palangka Raya.